Evaluation of mechanical strain resulting from working with two locally fabricated engine powered stationary grain thresher (2020)
In place of the combine harvesters, stationary grain threshers are the most common among the farmers in the developing countries, many are being produced locally to meet up with the local demands by the farmers which they find to be relatively cheap and affordable. To ascertain the level of their user friendliness, two threshers of heights 92 cm (M1) and 161.5 cm (M2) with capacities 3000kg/hr. and 6500kg/hr. respectively were selected for evaluation to determine the possible biomechanical strain that may result from working with these locally fabricated threshers. Questionnaire and physical measurements were employed for data collection of thirteen randomly selected operators, with ages ranged in-between 20 and 35 years. The results of machine performance tests showed that quantity threshed on average ± SD per minute are 12.59kg ± 2.41 (M1) and 20.38kg ± 3.84 (M2),corresponded to the mean (SD) of weight per lift of 1.75kg (0.44) and 2.06 (0.22), and mean; SD of frequency of lift/minute of 7lift/min;1.59 and 10lift/min;1.81. The body kinematics analysis showed flexion, extension, lateral deviation and abduction with respective highest mean values of 167.750 at kneel (M1), 111.500 at ankle (M1), 24.750 at neck (M2) and 72.000 at shoulder (M2) at the end of lift. Regression analysis of biomechanical parameters, and frequency of lift and weight per lift gave F-value of 425.987 (R2 =0.974), which shows no relationship at α= 0.01. Subjects’ indications of body parts discomforts showed highest percentages of 78.3%; 84.6% and 72.9%; 80.8% for M1; M2 at shoulder and lower back respectively. Conclusively, the overall result showed that the two machines need to be ergonomically modified to prevent the users from the risk of musculoskeletal disorder (MD).